Intervensi Pendidikan Kesehatan tentang Dermatitis Kontak terhadap Peningkatan Pengetahuan pada Pekerja Pencuci Mobil - Parinduri, Anggi Isnani; Siregar, Annisa Febriana (Jurnal Riset Hesti Medan, 2020)
Occupational disease is an artificial disease or man made disease. Occupational contact dermatitis is one of the most common occupational skin diseases, car wash workers are at risk of getting contact dermatitis because in the long term they have direct contact with chemicals during the work process. The purpose of this study was to determine the effect of health education interventions on contact dermatitis using flip chart media on increasing knowledge of car wash workers. The type of research used is quasi-experimental research with a one group pre-test-post-test design research design. The population of this research is car wash workers who are in Pangkalan Masyhur Village, Medan Johor City Medan, totaling 52 people. by using primary data and secondary data. The data analysis used in this study consisted of univariate and bivariate analyzes. This analysis uses descriptive statistics to describe the frequency distribution of the independent and dependent variables which are presented in tabular form. The bivariate analysis used in this study was the paired sample t-test. The results showed that there were differences in knowledge of car wash workers before and after health education interventions regarding contact dermatitis and health education interventions using flip chart media about contact dermatitis had an effect on increasing knowledge of washing workers. cars in the Pangkalan Masyhur Urban Village, Medan City in 2020.